Os cordis of mature Dromedary camel heart (Camelus dromedaries) with special emphasis on cartilago cordis - Balah, Ahmad; Bareedy, Mohamed Hafez; Abuel-Atta, Ahmad Awad; Ghonimi, Wael (Journal of Advanced Veterinary and Animal Research, 2014)
The present study was conducted to investigate the bony structure (i.e., os cordis) in the heart of mature Dromedary camel. Ten hearts were collected from healthy mature camels of both sexes aging between 7-9 years. Grossly, the heart contained one large, elongated bone that was embedded inside the heart wall where the cardiac muscles were inserted and fixed. The bony structure was located at the adjacent areas between aorta and atria. Also, it was lying in the atrioventricular plane near the junction of the interatrial and interventricular septa, and was extended anteriorly into the atrioventricular valve rings. Histologically, the os cordis was composed of fibrous connective tissue, small foci and pieces of hyaline cartilage, calcified cartilage, and a large piece of spongy bone. The spongy bone contained red and white bone marrows with numerous red blood cells, adipocytes and osteocytes. This is the first detail study on os cordis of Dromedary camel heart with special reference to cartilago cordis. DOI: http://dx.doi.org/10.5455/javar.2014.a26 J. Adv. Vet. Anim. Res., 1(3): 130-135, September 2014